2014
DOI: 10.1371/journal.pone.0106906
|View full text |Cite
|
Sign up to set email alerts
|

Wolfram Syndrome in the Japanese Population; Molecular Analysis of WFS1 Gene and Characterization of Clinical Features

Abstract: BackgroundWolfram syndrome (WFS) is a recessive neurologic and endocrinologic degenerative disorder, and is also known as DIDMOAD (Diabetes Insipidus, early-onset Diabetes Mellitus, progressive Optic Atrophy and Deafness) syndrome. Most affected individuals carry recessive mutations in the Wolfram syndrome 1 gene (WFS1). However, the phenotypic pleiomorphism, rarity and molecular complexity of this disease complicate our efforts to understand WFS. To address this limitation, we aimed to describe complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 29 publications
8
54
1
5
Order By: Relevance
“…La mayoría de las mutaciones son únicas para un individuo o una familia, por lo que su naturaleza privada hace muy difícil el delinear una clara relación genotipo-fenotipo 32,56,57 . Las mutaciones se distribuyen aleatoriamente en toda la secuencia codificante del gen, pero hasta el 80% de las mutaciones reportadas hasta la fecha se encuentran en el exón 8 25,26,30,31,37,[56][57][58][59] . En este estudio, el 60% de los pacientes (n = 3) cuentan con diagnóstico molecular y se trata de tres hermanos (los tres hombres del estudio) que presentan dos mutaciones en estado heterocigoto: la primera, heredada del padre, es una transición de guanina por citocina en el codón 177 que cambia una arginina por una prolina en el exón 5, y la segunda es una deleción de herencia materna de 16 pb (P451fsX515) en el exón 8 que cambia el marco de lectura y genera un codón de terminación prematura en la secuencia normal de la proteína.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La mayoría de las mutaciones son únicas para un individuo o una familia, por lo que su naturaleza privada hace muy difícil el delinear una clara relación genotipo-fenotipo 32,56,57 . Las mutaciones se distribuyen aleatoriamente en toda la secuencia codificante del gen, pero hasta el 80% de las mutaciones reportadas hasta la fecha se encuentran en el exón 8 25,26,30,31,37,[56][57][58][59] . En este estudio, el 60% de los pacientes (n = 3) cuentan con diagnóstico molecular y se trata de tres hermanos (los tres hombres del estudio) que presentan dos mutaciones en estado heterocigoto: la primera, heredada del padre, es una transición de guanina por citocina en el codón 177 que cambia una arginina por una prolina en el exón 5, y la segunda es una deleción de herencia materna de 16 pb (P451fsX515) en el exón 8 que cambia el marco de lectura y genera un codón de terminación prematura en la secuencia normal de la proteína.…”
Section: Discussionunclassified
“…La prevalencia del SW se estima en 1 por 770,000 personas en el Reino Unido, con una prevalencia de portador de 1 en 354 24 , de 1 en 710,000 en la población japonesa 25 y de 1 en 805,000 en la India 26 . Se han descrito prevalencias más altas, como 1 en 68,000 personas en Líbano 27 , parcialmente atribuible a las altas tasas de consanguinidad en esta región.…”
Section: Introductionunclassified
“…However, detailed data on the psychiatric phenotype are still rare. Several authors reported psychotic symptoms, attempted suicide, violent behavior, and affective disorders (e.g., mixed mood swings), in WS homozygous patients (Swift and Swift 2000;Matsunaga et al 2014;Ramli et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1:710.000 (1). The disease is also known as the DIDMOAD syndrome (diabetes insipidus, diabetes mellitus, optic atrophy, deafness).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is also known as the DIDMOAD syndrome (diabetes insipidus, diabetes mellitus, optic atrophy, deafness). Most of the individuals afflicted with this disease have the recessive mutation in the WFS gene 1 (WFS1, 4p16.3) (1,2) and rarely in the WFS gene 2 (WFS2) (3). A dominant mutation in the WFS1 gene was also described in connection with sensorineural hearing loss, deafness, and optic atrophy [Wolfram-like syndrome (WFSL)] (4).…”
Section: Introductionmentioning
confidence: 99%